Closed-Loop Test Based Parametric Independent Control of DC–DC Boost-Converter Using Two Degree of Freedom Internal Model Control Scheme - Mantu Kumar Ram (17949257) (2023)
In this manuscript, parametric independent control of DC-DC boost converter using two degree of freedom internal model control scheme has been proposed. The control scheme can handle the set-point and the load-disturbance response separately. A simple closed-loop set-point experiment is utilized to obtain the transfer function model of the boost-converter which make the control scheme independent of circuit parameter information as well as unknown load. This scheme results into improved output voltage control of DC-DC boost-converter which is required in several applications such as solar PV systems, energy storage systems and electrical vehicles. The controller in this scheme have been designed through direct synthesis approach in frequency domain. A dedicated hardware set up is used to validate the proposed controller. The satisfactory regulatory performance of the boost-converter has been obtained. A comparative analysis of this scheme with recently reported work has also been presented. The proposed scheme is robustly stable and it can bear upto 30% change in modelling uncertainty. Other Information Published in: IEEE Access License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1109/access.2023.3297491